Establishing a methodology to measure vulnerability of unhoused populations to climate change in the United States - Harris R. Eisenhardt; Thomas Peterson; Michael Schwebel (Climate Risk Management, 2024)
The interactions between climate change and homelessness in the United States are neither widely documented nor uniformly quantified. Individuals who experience homelessness are commonly not accounted for in community, state, or federal climate change adaptation planning or vulnerability assessment frameworks. Drawing on established vulnerability assessment publications, this review and analysis presents a standard approach to evaluate the climate vulnerability of an unhoused population, modeled at U.S. census tract granularity. The methodology features recommended steps to leverage modeling-, survey-, and evaluation-based indicators to measure exposure, sensitivity, and adaptive capacity to determine vulnerability of an unhoused population to relevant climate impact drivers. Standardizing a vulnerability assessment methodology that prioritizes unhoused populations can facilitate new opportunities for data compilation, enabling assessment practitioners to highlight urgent vulnerability gaps and undertake targeted interventions to improve resilience within an unhoused population.